If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(2 + -1(2x + -4)) = 2(-3 + -3x) Reorder the terms: 6(2 + -1(-4 + 2x)) = 2(-3 + -3x) 6(2 + (-4 * -1 + 2x * -1)) = 2(-3 + -3x) 6(2 + (4 + -2x)) = 2(-3 + -3x) Combine like terms: 2 + 4 = 6 6(6 + -2x) = 2(-3 + -3x) (6 * 6 + -2x * 6) = 2(-3 + -3x) (36 + -12x) = 2(-3 + -3x) 36 + -12x = (-3 * 2 + -3x * 2) 36 + -12x = (-6 + -6x) Solving 36 + -12x = -6 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 36 + -12x + 6x = -6 + -6x + 6x Combine like terms: -12x + 6x = -6x 36 + -6x = -6 + -6x + 6x Combine like terms: -6x + 6x = 0 36 + -6x = -6 + 0 36 + -6x = -6 Add '-36' to each side of the equation. 36 + -36 + -6x = -6 + -36 Combine like terms: 36 + -36 = 0 0 + -6x = -6 + -36 -6x = -6 + -36 Combine like terms: -6 + -36 = -42 -6x = -42 Divide each side by '-6'. x = 7 Simplifying x = 7
| 5+2d=9 | | 17-4d=5 | | -5(2t-5)+8t=5t-8 | | 3x^2-45x+70=0 | | -2x=-4(-3)-4 | | 4w+3=-25 | | -2x=-4(-3)3-4 | | 4.6=-7+x | | -2x=-4-3-4 | | -f(x)=45+10x | | 2x-9x-2=31 | | -2x=-4X-3-4 | | 1.4*x^2+840=x^2+1200 | | 9x+2=9(x+8) | | 3x+5y-78=9988.98 | | x/3-x/5=2/3 | | x^3+9x= | | 2x+y=4.6 | | 10+2p=18 | | Y=38-2x | | x+2(5+x)= | | 20+(-3)= | | -22-5= | | -5(7-8x)=37 | | 1.4*x^2-360=x^2 | | 3x-(x+3)=16-4x | | (18.6*d)*1= | | 5(9x-4)=2h | | log(x)+log(2)=3 | | 5x^2+15-90=0 | | 6+2(x-1)= | | Ac+3b=2f |